Q: 1 squared plus 1 squared plus 2 squared plus 3 squared plus 5 squared plus 8 squared equals?

Write your answer...

Submit

Related questions

1^2 + 1^2 + 1^2 + 1^2 + 1^2 + 1^2 = 1 + 1 + 1 + 1 + 1 + 1 = 5

1/2 = 25/50

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

2 squared plus 2 squared equals 16 because 2 squared is 4 times 4 equals 16. Math: 4x4=16 so your answer is 16 :)!

y-1=(x-2)^1/2

b = sqrt32 or 4 root 2

yes 1 + cot x^2 = csc x^2

No because no 2 numbers can be squared to equal 4. 1 squared is 1 2 squared is 4 so the lowest answer is 5.

F(x)=[x^2]+1

X=1/2

The Pythagoream Thereom is a^2 + b^2 = c^2. Written out it is a squared plus b squared equals c squared.

equals 2 p squared

no if 1 plus 1 equals 2 then 2 plus 2 equals 4.

Simple equation lad. In your example, you said n=4 and x= n squared + n - 1 + (n-2)squared + (n-3)squared. You simply write n²+n-1+(n-2)²+(n-3)² I hope that is what you mean by what you say. P.S. To get the to the power of sign, hold alt and press 0178 for ², and 0179 for ³

4(w^2 + 3w + 1)

The missing number is 49. This is why: 1 plus 2 equals 3, then 3 squared is 9. 2 plus 3 equals 5, then 5 squared is 25. Therefore, the missing number must be 49 to make the number sentence (3 plus 4 equals 7, then 7 squared is 49) true.

No, (sinx)^2 + (cosx)^2=1 is though

3(2x - 1)(x - 2)

(2x + 1)(2x + 1) or (2x + 1)2 so x = -0.5

x is negative 1x is negative 2

The Pythagoream Thereom is a^2 + b^2 = c^2. Written out it is a squared plus b squared equals c squared.

If I have this correct you are asking x^2 + 10^2 = 12^2 Then x=6.633249507108

1 squared plus 8 squared or 4 squared plus 7 squared

a number equals 2

x3+3x2+3x+2 divided by x+2 equals x2+x+1